A Practically Method to Modify Shallow Foundation for Supporting Multy-Storeyed Building with CPT Data Tests - Irnawaty, Irnawaty; Suyuti, Suyuti; Tata, Arbain; Ibrahim, Maulana (TECHNO: JURNAL PENELITIAN, 2025)
A foundation aims to distribute upper structure loads as dead, live, and earthquake loads. A construction of medical building four stories called Mother and Children of RSUD Chasan Boisoirie as official hospital in Ternate city. Design of sub-structure results of the consulting were worked with shallow foundation with width B is the length (L) of 2,0 meters and depth (Df) of 3,6m in field. However, condition was conducted by reinforcing and casting concrete for the foundation. There are some problems, i.e., ratio of foundation depth to the width B (λ) of 1,8 1,0. That can be collapsed of footing of foundation structure due to such shear punch due to an earthquake. Therefore, this research is followed National such as standard SNI, loading due to earthquake, learning CPT secondary data, checking soil layer data in the field, determining shear stress of foundation modification, checking soil stress beneath the foundation footing and calculation of the ground's flexural bar. Finally, the simulation results are given load as moment-x (Mx) of 23,97 tons, moment-y (My) of 23,86 tons and vertical load (Puv) of 201,7 ton. Determining results of shear strength (ϕVnp) of 3.097,6 kN 2017 kN (safe). Calculation is given a maximum stress of soil layer beneath foundation checked by σmax of 863 kN/m2 qan of 1.677,6 kN/m2. Flexible bars for footing foundation due to vertical load and response of the subsoil layer were saved in controlled criteria.